Autonomous vehicles and systems : a technological and societal perspective - Sethi, Ishwar K., 1948- (River Publishers series in automation, control and robotics., 2023)
This book captures multidisciplinary research encompassing various facets of autonomous vehicle systems (AVS) research and developments. The AVS field is rapidly moving towards realization with numerous advances continually reported. The contributions to this field come from widely varying branches of knowledge, making it a truly multidisciplinary area of research and development. The topics covered in the book include: • AI and deep learning for AVS • Autonomous steering through deep neural networks • Adversarial attacks and defenses on autonomous vehicles • Gesture recognition for vehicle control • Multi-sensor fusion in autonomous vehicles • Teleoperation technologies for AVS • Simulation and game theoretic decision making for AVS • Path following control system design for AVS • Hybrid cloud and edge solutions for AVS • Ethics of AVS.